A new lifetime model with regression models, characterizations and applications. Issue 1 (2nd January 2019) - Yousof, Haitham M.; Altun, Emrah; Rasekhi, Mahdi; Alizadeh, Morad; Hamedani, G. G.; Ali, M. Masoom
ABSTRACT: In this article, we introduce a new extension of Burr XII distribution called Topp Leone Generated Burr XII distribution. We derive some of its properties. Useful characterizations are presented. Simulation study is performed to assess the performance of the maximum likelihood estimators. Censored maximum likelihood estimation is presented in the general case of multi-censored data. The new location-scale regression model based on the proposed distribution is introduced. The usefulness of the proposed models is illustrated empirically by means of three real datasets.